Hepatocyte Growth Factor Effects on Mesenchymal Stem Cells Derived from Human Arteries: A Novel Strategy to Accelerate Vascular Ulcer Wound Healing - Sabrina Valente; Carmen Ciavarella; Emanuela Pasanisi; Francesca Ricci; Andrea Stella; Gianandrea Pasquinelli (Stem Cells International)
Vascular ulcers are a serious complication of peripheral vascular disease, especially in diabetics. Several approaches to treat the wounds are proposed but they show poor outcomes and require long healing times. Hepatocyte Growth Factor/Scatter Factor (HGF/SF) is a pleiotropic cytokine exerting many biological activities through the c-Met receptor. This study was aimed at verifying whether HGF/SF influences proliferation, migration, and angiogenesis on mesenchymal stem cells isolated from human arteries (hVW-MSCs). hVW-MSCs were exposed to NIBSC HGF/SF (2.5, 5, 10, and 70 ng/mL) from 6 hrs to 7 days. HGF and c-MET mRNA and protein expression, cell proliferation (Alamar Blue and Ki–67 assay), migration (scratch and transwell assays), and angiogenesis (Matrigel) were investigated. hVW-MSCs displayed stemness features and expressed HGF and c-MET. HGF/SF did not increase hVW-MSC proliferation, whereas it enhanced the cell migration, the formation of capillary-like structures, and the expression of angiogenic markers (vWF, CD31, and KDR). The HGF/SF effects on hVW-MSC migration and angiogenic potential are of great interest to accelerate wound healing process. Local delivery of HGF/SF could therefore improve the healing of unresponsive vascular ulcers.